The implications of inefficient markets for executive pay comparison: The case of China and Poland - Liu, Yanqiu; Liu, Hanmin (Frontiers in Psychology, 2022)
Although there is a large volume of literature on executive compensation, few of these studies concentrate on executive pay comparisons, and research on the antecedents of executive pay compensation behavior has never been addressed. This paper fills this gap in executive compensation comparison literature by beginning with an executive compensation comparison, and then the elements that influence executive pay comparison behaviors are discussed. The findings of this study confirm that executive pay comparison behaviors exist in both China and Poland, and this confirmation was made using face-to-face questionnaires in both countries. In addition, the findings indicate that the influence factors are different. There is a significant relationship between executive compensation comparison and a dysfunctional agent market, herd mentality in China. And in Poland, there is a significant relationship between executive compensation comparison and ineffectiveness of government intervention, herd mentality. The implications of the study are also discussed.